The Implementation of Conjugate Gradient Methods for Data Fitting - N. Zullpakkal; N. Shapie; S.F. Husin; W. Khadijah; N.A. Salahudin; S.M. Zokri; M.N. Rashidi (Universiti Malaysia Pahang Al-Sultan Abdullah Publishing, 2024)
Non-Indexed Publication